Chassis engineering of Escherichia coli for trans‐4‐hydroxy‐l‐proline production. Issue 2 (12th May 2020) - Chen, Xiulai; Yi, Juyang; Song, Wei; Liu, Jia; Luo, Qiuling; Liu, Liming
Summary: Microbial production of trans ‐4‐hydroxy‐l ‐proline (Hyp) offers significant advantages over conventional chemical extraction. However, it is still challenging for industrial production of Hyp due to its low production efficiency. Here, chassis engineering was used for tailoring Escherichia coli cellular metabolism to enhance enzymatic production of Hyp. Specifically, four proline 4‐hydroxylases (P4H) were selected to convert l ‐proline to Hyp, and the recombinant strain overexpressing Ds P4H produced 32.5 g l −1 Hyp with α‐ketoglutarate addition. To produce Hyp without α‐ketoglutarate addition, α‐ketoglutarate supply was enhanced by rewiring the TCA cycle and l ‐proline degradation pathway, and oxygen transfer was improved by fine‐tuning heterologous haemoglobin expression. In a 5‐l fermenter, the engineered strain E. coli Δ sucCD Δ putA ‐VHb(L) ‐ Ds P4H showed a significant increase in Hyp titre, conversion rate and productivity up to 49.8 g l −1, 87.4% and 1.38 g l −1  h −1 respectively. This strategy described here provides an efficient method for production of Hyp, and it has a great potential in industrial application. Abstract : Microbial production of trans ‐4‐hydroxy‐l ‐proline (Hyp) offers significant advantages over conventional chemical extraction. Here, chassis engineering was used for tailoring Escherichia coli cellular metabolism to enhance enzymatic production of Hyp. In a 5‐l fermenter, the engineered strain showed a significant increase in Hyp titer, conversion rate, and productivity up to 49.8 g l −1, 87.4%, and 1.38 g l −1  h −1, respectively.